Reaction time, performance and level of physiological arousal - Ellis-Smith, Michael John (Department of Psychology, 2016)
30 Male Students were used as subjects in a study to assess the effects of physiological arousal, induced by means of a placebo injection, upon visual reaction· time. Two levels of task difficulty were employed: a two-choice test requiring manual responses and a four-choice test, in which the additional two peripheral stimuli were responded to by foot pedals. Manifest Anxiety scores were used as a means to categorize subjects and allow for individual differences. EEG was monitered as a controlling measure for each subject. Pulse rates, palmar sweat index and blood pressures were used as measures of physiological arousal. Results were interpreted in terms of the YerkesDodson principle.